Is an artificial limb embodied as a hand? Brain decoding in prosthetic limb users - Maimon-Mor, Roni O. (PLoS Biol, 2020)
The potential ability of the human brain to represent an artificial limb as a body part (embodiment) has been inspiring engineers, clinicians, and scientists as a means to optimise human–machine interfaces. Using functional MRI (fMRI), we studied whether neural embodiment actually occurs in prosthesis users’ occipitotemporal cortex (OTC). Compared with controls, different prostheses types were visually represented more similarly to each other, relative to hands and tools, indicating the emergence of a dissociated prosthesis categorisation. Greater daily life prosthesis usage correlated positively with greater prosthesis categorisation. Moreover, when comparing prosthesis users’ representation of their own prosthesis to controls’ representation of a similar looking prosthesis, prosthesis users represented their own prosthesis more dissimilarly to hands, challenging current views of visual prosthesis embodiment. Our results reveal a use-dependent neural correlate for wearable technology adoption, demonstrating adaptive use–related plasticity within the OTC. Because these neural correlates were independent of the prostheses’ appearance and control, our findings offer new opportunities for prosthesis design by lifting restrictions imposed by the embodiment theory for artificial limbs.